2020
DOI: 10.3390/ani10010137
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dietary Supplementation of Lactic Acid Bacteria Fermented Rapeseed with or without Macroalgae on Performance and Health of Piglets Following Omission of Medicinal Zinc from Weaner Diets

Abstract: The feeding of medicinal zinc oxide (ZnO) to weaner piglets will be phased out after 2022 in Europe, leaving pig producers without options to manage post-weaning disorders. This study assessed whether rapeseed meal, fermented alone (FRM) or co-fermented with a single (Ascophylum nodosum; FRMA), or two (A. nodossum and Saccharina latissima; FRMAS) brown macroalagae species, could improve weaner piglet performance and stimulate intestinal development as well as maturation of gut microbiota in the absence of in-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 72 publications
1
38
0
1
Order By: Relevance
“…In the current study, FRM demonstrated the same desirable effects on ADG, and intestinal development and barrier function as we have previously observed and optimum effects were observed when 8% or 10% FRM was included in the weaner diets [14]. Similar improvements in ADG upon dietary addition of FRM in broiler chicken [27] and fermented soybean meal in piglets [28,29] were reported in other studies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, FRM demonstrated the same desirable effects on ADG, and intestinal development and barrier function as we have previously observed and optimum effects were observed when 8% or 10% FRM was included in the weaner diets [14]. Similar improvements in ADG upon dietary addition of FRM in broiler chicken [27] and fermented soybean meal in piglets [28,29] were reported in other studies.…”
Section: Discussionsupporting
confidence: 88%
“…We have also previously tested FRM or rapeseed meal co-fermented with the brown macroalgae Ascophyllum nodosum (AN) and or Saccharina latissima (SL) in weaned piglets where 10% FRM inclusion improved growth performance, intestinal health and colon microbiota. However, the inclusion of either AN or AN plus SL in FRM resulted in inconsistent and contradictory findings between growth performance and gut health indices [14].…”
Section: Introductionmentioning
confidence: 99%
“…Litter weights during the nursing period were recorded every week, and feed intake was recorded daily. Performance indicators such as body weight, ADFI (average daily feed intake), average daily weight gain (ADG), feed conversion ratio (FCR) and completion rate were calculated at the pen level as previously outlined (Satessa et al 2020a).…”
Section: Feeding and Recording Of Piglet Performancementioning
confidence: 99%
“…It is the most stressful period in a pig's life and often lead to morbidities like diarrhea. In-feed zinc-oxide used to be a prevalent choice for prophylaxis, but according to the European Union regulations, zinc-oxide shall no longer be directly used in feed or water from 2022 (Satessa et al 2020a). This leaves an urgent need for new prophylactic substitutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation